Multigenic Control of Pod Shattering Resistance in Chinese Rapeseed Germplasm Revealed by Genome-Wide Association and Linkage Analyses - Liu, Jia; Wang, Jun; Wang, Hui; Wang, Wenxiang; Zhou, Rijin; Mei, Desheng; Cheng, Hongtao; Yang, Juan; Raman, Harsh; Hu, Qiong (Frontiers in Plant Science, 2016)
Majority of rapeseed cultivars shatter seeds upon maturity especially under hot-dry and windy conditions, reducing yield and gross margin return to growers. Here, we identified quantitative trait loci (QTL) for resistance to pod shatter in unstructured diverse panel of 143 rapeseed accessions, and two structured populations derived from bi-parental doubled haploid (DH) and inter-mated (IF2) crosses derived from R1 (resistant to pod shattering) and R2 (prone to pod shattering) accessions. Genome-wide association analysis identified six significant QTL for resistance to pod shatter located on chromosomes A01, A06, A07, A09, C02 and C05. Two of the QTL, qSRI.A09 delimited with the SNP marker Bn-A09-p30171993 (A09) and qSRI.A06 delimited with the SNP marker Bn-A06-p115948 (A06) could be repeatedly detected across environments in diversity panel, DH and IF2 populations, suggesting that at least two loci on chromosomes A06 and A09 were the main contributors to pod shatter resistance in Chinese germplasm. Significant SNP markers identified in this study especially those appeared repeatedly across environments provide a cost-effective and an efficient method for introgression and pyramiding of favorable alleles for pod shatter resistance via marker-assisted selection in rapeseed improvement programs.